Slow scholarship in writing retreats: A diffractive methodology for response-able pedagogies - Bozalek, V. (South African Journal of Higher Education, 2017)
The corporatization of universities has led to increasing pressure on academics to publish as quickly and prolifically as possible. Writing retreats have been used as one way of ensuring the production of academic papers by providing spaces for academics to write, and pressurizing them to publish shortly thereafter. This paper provides an alternative way of viewing and conducting writing retreats – that of Slow scholarship, which foregrounds attentiveness, care, thoughtfulness and quality rather than quantity and production. A ‘response-able’ pedagogy is suggested as a way of enacting a Slow scholarship, using a diffractive methodology for reading and writing and responding to peers’ writing at writing retreats.